Characterization of the Prognostic m6A-Related lncRNA Signature in Gastric Cancer - Wang, Haixu; Meng, Qingkai; Ma, Bin (Frontiers in Oncology, 2021)
N6-methyladenosine (m6A) is a common form of mRNA modification regulated by m6A RNA methylation regulators and play an important role in the progression of GC. However, the prognostic role of m6A-related lncRNA in gastric cancer (GC) have not been fully explored. This study aimed at exploring biological function and prognostic roles of m6A-related lncRNA signature in GC. A total of 800 m6A-related lncRNAs were identified through Person correlation analysis between m6A regulators and all lncRNAs. 11 m6A-related lncRNA signature were identified through survival analysis and the Kaplan-Meier (KM) curve analysis result suggesting that patients in the low risk group have a significantly better overall survival (OS) and disease free survival (DFS) outcome than the high risk group. Also, the lncRNA signature can serve as an independent prognostic factor for OS and DFS survival. The gene set enrichment analysis (GSEA) result suggesting that patients in the high risk group were mainly enriched in ECM receptor interaction, focal adhesion, and cytokine-cytokine receptor interaction pathway, while the low risk group was characterized by the base excision repair pathway. We further constructed a individualized prognosis prediction model via the nomogram based on the independent prognostic factor for the OS and DFS, respectively. In addition, some candidate drugs that aimed at GC risk group differentiation were identified by using the Connective Map (CMap) database. Lastly, four subgroups (C1, C2, C3, and C4) were identified based on the m6A-related lncRNA expression through consensus clustering algorithm. Among them, subgroup C1 and C2 responded well to immunotherapy, compared to subgroup C3 and C4, suggesting that the C1 and C2 subgroup might benefit from the immunotherapy. In conclusion, the m6A-related lncRNA signature can independently predict the OS and DFS of GC, and may aid to develop a personalized immunotherapy strategy.